CD147 immunohistochemistry discriminates between reactive mesothelial cells and malignant mesothelioma - Pinheiro, Céline (2012)
Malignant mesothelioma (MM) is a rare form of cancer. Its histopathological diagnosis is very difficult, as it exhibits a number of different appearances that can be misinterpreted as metastatic invasion or atypical hyperplasia. Thus, there is an urgent need to identify adequate markers to distinguish between benign and malignantcells, allowing the implementation of appropriate therapies and, possibly, specific directed therapies. MM, like other tumors, show an increase in glucose uptake, due to high rates of glycolysis, inducing an intracellular overload of acids. In this context, monocarboxylate transporters (MCTs) emerge as important players, by mediating the transmembranar co-transport of lactate with a proton, thereby, regulating pH and allowing continuous glycolysis. Importantly, proper MCT expression and activity depend on its coexpression with a chaperone, CD147, which is associated with poor prognosis in cancer. Twenty-two samples including reactive mesothelial cells, MM, and atypical mesothelial hyperplasias were evaluated for immunoexpression of MCT1, MCT4, and CD147. Expression of these proteins was compared with GLUT1 as a new promising marker for MM. Although MCT isoforms were not differentially expressed in the two types of cytological specimens, CD147, as GLUT1, was almost exclusively expressed in MM. Both MCT1 and MCT4 are not able to discriminate between mesothelial reactive cells and mesothelial malignant cells, while CD147 was able to distinguish these two proliferations. If confirmed, besides being a good marker for identification of MM, CD147 may also be a target for therapeutical strategies in this rare type of tumor.